(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article is about the great poet of the Kazakh people Abai Kunanbaev’s creative connection with the Russian literature. The influence of Russian poetry is thoroughly analyzed in the poems of the author. Abai Kunanbaev translated poems of Russian poets. This shows his contribution to the Kazakh poetry. The ways of improvement and achievement of author’s works are considered in the article. M. Auezov states that Lermontov’s lyrics has here enormous influence on Abai. This was Abai’s first poem where he changed rhythm of each line, syllable division immensely, sometimes his poems consist of fourfive words, even there are moments when one word makes one line. We can also see that Russian literature’s a profound impact on Abai’s poem «When a shadow lengthens». According to М.Auezov this poem takes a special place among those written with a realistic tradition. The author depicts four seasons and tries to connect them with his feelings. It is normal that Russian’s literature affected Abai’s translations.